Mobile money mitigates the negative effects of weather shocks: Implications for risk sharing and poverty reduction in Bangladesh - Matsuura, Masanori; Islam, Abu Hayat Md. Saiful; Tauseef, Salauddin (Asian Development Bank, 2023)
Frequent weather shocks stemming from global climate change are significant for rural and poor households. Floods deprive households’ assets and agricultural production, resulting in a reduction of household income. Moreover, droughts substantially reduce crop yields, inducing food insecurity. For example, South Asian countries confront various climate risks such as extreme floods and cyclones with the idiosyncrasies of summer and monsoon rainfall having short- and long-term impacts on the lives of more than 1 billion people (Turner and Annamalai 2012). To cope with climate shocks, adaptive strategies are urgently needed. Existing literature points to the potential effectiveness of financial services, such as microfinance and weather index insurance, in response to the shocks. Rural financial services challenge transaction costs that render markets for financial services costly or missing. The emergence of digital technologies such as mobile phones and mobile or digital money recreate rural markets for savings, credit, and insurance services, especially in developing economies. In recent years, mobile phones have been widely adopted in developing countries contributing to economic growth. Bangladesh has also experienced an expansion of mobile phone subscriptions. This in turn has led to the development of mobile money services enabling people to transfer, deposit, and withdraw money from an online account without having a bank account (Suri et al. 2023). Mobile money greatly reduces transaction costs, while enhancing the convenience, security, and time taken for transactions. Since mobile money allows people to transfer and deposit money using short message services without access to the internet and overcomes the challenges of formal insurance, it is important that we examine how mobile money can help households smooth their consumption in Bangladesh where the number of mobile cellular subscriptions per 100 people was over 100 in 2020, but the ratio of individual internet users remained at only 25% in 2020.